2021
DOI: 10.3390/ijms22147459
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Signaling Acts as a Marker for Environmental Stressors in Zebrafish

Abstract: The oxytocin system plays a role in stress responses and behavior modulation. However, the effects of oxytocin signaling on stress adaptation remain unclear. Here, we demonstrated the roles of oxytocin signaling as a biomarker under stress conditions in the peripheral tissues (the gills) and central nervous system (the brain). All the environmental stressors downregulated the expression of oxytocin receptors in the gills, and the alteration of the expression of oxytocin receptors was also found in the brain af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 100 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…Therefore it is important to further link neural circuits displaying aberrant activity, with excessive IL-1β expression within SDMN regions, in MK-801-treated fish. Toward that direction, Dm a putative homologous to the mammalian basolateral amygdala (BLA) and PM, a part of the preoptic area, are key nodes in the SDMN ( O'Connell and Hofmann, 2011 ), regulate both social behavior ( Bickart et al, 2014 ; Nunes et al, 2021 ) as well as fear and anxiety-related responses ( Lal et al, 2018 ; Chuang et al, 2021 ), so it is logical to considered as targets of great importance. The enhanced expression of IL-1β may alter synaptic plasticity in these brain regions, contributing to social impairments and anxiety-like behavior, observed in MK-801-treated fish.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is important to further link neural circuits displaying aberrant activity, with excessive IL-1β expression within SDMN regions, in MK-801-treated fish. Toward that direction, Dm a putative homologous to the mammalian basolateral amygdala (BLA) and PM, a part of the preoptic area, are key nodes in the SDMN ( O'Connell and Hofmann, 2011 ), regulate both social behavior ( Bickart et al, 2014 ; Nunes et al, 2021 ) as well as fear and anxiety-related responses ( Lal et al, 2018 ; Chuang et al, 2021 ), so it is logical to considered as targets of great importance. The enhanced expression of IL-1β may alter synaptic plasticity in these brain regions, contributing to social impairments and anxiety-like behavior, observed in MK-801-treated fish.…”
Section: Discussionmentioning
confidence: 99%
“…The use of RNA in situ hybridization on adult brain demonstrated an upregulation of oxt in the anterior part of the parvocellular preoptic nucleus (PPa). It expresses several neurohormones such as oxytocin or arginine-vasopressin with conserved function compared to mammals [ 103 ] such as the regulation of water homeostasis [ 104 ], the control of blood pressure [ 105 ] as well as a role in social behavior and the regulation of anxiety [ 49 , 50 , 106 ]. Interestingly, a recent analysis of the stress response in zebrafish correlated to the increased number of oxytocinergic cells in the brain with environmental stress provoked by immersion in deionized water for 24 h [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…It expresses several neurohormones such as oxytocin or arginine-vasopressin with conserved function compared to mammals [ 103 ] such as the regulation of water homeostasis [ 104 ], the control of blood pressure [ 105 ] as well as a role in social behavior and the regulation of anxiety [ 49 , 50 , 106 ]. Interestingly, a recent analysis of the stress response in zebrafish correlated to the increased number of oxytocinergic cells in the brain with environmental stress provoked by immersion in deionized water for 24 h [ 50 ]. Other experiments in rodents revealed that repeated defeat experiences increased the number of oxytocinergic neurons in the PVN as well as after chronic homotypic stress [ 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a mechanistic point of view, smoking-induced alterations in HPA axis activity might account for this association. Elevated cortisol levels in smokers versus non-smokers are well-established [ 57 ] and preclinical research demonstrated that environmental stressors downregulate OXTR expression in both peripheral and brain tissues of zebrafish [ 58 ]. On the other hand, Kanamori et al [ 59 ] reported increased OXTR concentrations in the uterine myometrium in smoking versus non-smoking pregnant women and positive correlations with the number of daily cigarettes consumed and the concentration of exhaled carbon monoxide.…”
Section: Discussionmentioning
confidence: 99%